(untitled) (Bioscience Journal, 2022)
The aim of this randomized double-blinded study was to evaluate the enamel surface roughness and color change after one month of whitening toothpaste use and the color stability obtained 1 month after its interruption. 30 volunteers were divided into 3 groups (n = 10) corresponding to the dentifrices: 1) Colgate Total 12 Clean Mint (TD) (Control), 2) Colgate Luminous White (LW) and 3) Sensodyne Whitening Extra Fresh (SB). The volunteers were impression with addition silicone to obtain an epoxy resin replica of the upper central incisor for the initial surface roughness evaluation using a profilometer and the initial color of the incisors and canines was evaluated with a spectrophotometer after one week of wash-out. After 1 month, the color of the central incisors and canines was measured again, and the volunteers were molded to obtain a second replica to the final roughness analysis. Data were submitted to ANOVA-one way (p≤0.05). The results showed that there was no statistical difference between the dentifrices for color difference and surface roughness for all the studied conditions. It was possible to conclude that the whitening dentifrices used in this study were not able to alter the initial color of the teeth and did not cause changes in the surface roughness of enamel.